Becoming a Language Teacher in the Primary School - Briguglio, Carmela; Tognini, R.; Breen, M. (Australian Federation of Modern Language Teachers Associations Inc., 1997)
In this paper we describe a study which we carried out in 1995. The study examined the experiences and perceptions of a number of primary generalist teachers who had undertaken intensive methodology courses to become primary language teachers. It sought to explore the appropriateness of the methodology courses in preparing teachers for their new role and the impact on them of a change of role. It also aimed to provide information on the nature and type of support required by primary language teachers and on the conditions considered necessary for the establishment of successful language programs at the primary level.The paper is divided into five sections. In the first section we outline the context for the study, the objectives of the study, its research methodology and the characteristics of the sample of teachers studied. Section two presents the teachers' evaluations of the methodology courses and information about the professional development needs of teachers. The third section explores the teachers' experience of their change in role using the 'transition curve' model and examinesthe factors which helped and those which constrained teachers' capacity to adapt to this change in role. Section four presents the preferred conditions and support required by language teachers working in primary schools. In the fifth and final section we provide deductions from the findings of the study about the essential conditions for the establishment of an effective language program.Although the sample we studied consisted exclusively of teachers from Western Australia, we believe the research has implications for other Australian States and Territories which have implemented very similar strategies in order to augment the pool of primary teachers to enable the expansion of the teaching of languages at the primary level.